Anaesthetic Management of Tracheal Stenosis Posted for Resection and Reanastomosis: A Case Report - Parul Gupta; Ashish Yadav; Monika Bhandari; Kunika Tantia (Asian Journal of Medical Research, 2021)
A 38 years old male patient diagnosed with tracheal stenosis was posted for resection and anastomosis of the stenotic part. Keeping cardiothoracic surgeon on standby with femoral vessels ready for emergency bypass, awake fiberoptic intubation was done with cuffed flexometallic tube. After making a nick in the stenotic part by the surgeon, cuffed flexometallic tube of ID 4.5 mm was inserted in the distal part and further ventilation continued with that tube while leaving oroendotracheal tube in situ. At the end of surgery the surgeon had difficulty placing sutures around the large tube so ETT of smaller ID of 5mm was inserted after removing the previous ETT of ID 7.5 mm. Once the anastomosis was over, the tube was removed from the distal part of trachea and ventilation was continued from the oroendotracheal tube placed at the start of the procedure. The patient maintained well throughout the procedure. The patient was extubated uneventfully.